Characterisation of integrated WAAM and machining processes - Adebayo, Adeyinka (Cranfield University, 2013)
This research describes the process of manufacturing and machining of wire and arc additive manufactured (WAAM) thin wall structures on integrated and non¬integrated WAAM systems. The overall aim of this thesis is to obtain a better understanding of deposition and machining of WAAM wall parts through an integrated system. This research includes the study of the comparison of deposition of WAAM wall structures on different WAAM platforms, namely an Integrated SAM Edgetek grinding machine, an ABB robot and a Friction Stir Welding (FSW) machine. The result shows that WAAM is a robustly transferable technique that can be implemented across a variety of different platforms typically available in industry. For WAAM deposition, a rise in output repeatedly involves high welding travel speed that usually leads to an undesired humping effect. As part of the objectives of this thesis was to study the travel speed limit for humping. The findings from this research show that the travel speed limit falls within a certain region at which humping starts to occur. One of the objectives of this thesis was to study the effect of lubricants during sequential and non-sequential machining/deposition of the WAAM parts. Conventional fluid lubricants and solid lubricants were used. In addition, the effect of cleaning of deposited wall samples with acetone was also studied. A systematic study shows that a significant amount of solid lubricant contamination can be found in the deposited material. Furthermore, the results indicate that even cleaning of the wire and arc additive manufactured surfaces with acetone prior to the weld deposition can affect the microstructure of the deposited material.
Keywords: Wire and arc additive manufacturing; additive manufacturing; machining; solid lubricants; microstructure